Combined algicidal effect of urocanic acid, N-acetylhistamine and l-histidine to harmful alga Phaeocystis globosa. Issue 23 (3rd April 2018) - Zhuang, Luer; Zhao, Ling; Yin, Pinghe
Abstract : Ultrastructure of Phaeocystis globosa cells after treatment with EC50 value for 72 h: (a) control, (b) ace (16 μg mL −1 ), (c) uro (8 μg mL −1 ), (d) uro + ace (1 : 1 TU, 8 : 16 μg mL −1 ) Chl, chloroplast; CW, cell wall; N, nucleus; PM, plasma membrane. Abstract : The algicidal compounds produced by Bacillus sp. strain B1 against Phaeocystis globosa, one of the main red-tide algae, were isolated and identified in a previous study as urocanic acid (uro), l -histidine (his) and N -acetylhistamine (ace). The 96 h median effective concentration EC50 values indicated the algicidal effect order of uro (8 μg mL −1 ) > ace (16 μg mL −1 ) > his (23 μg mL −1 ). The interaction between uro and ace had a synergistic effect on Phaeocystis globosa, accelerated the increase in its intracellular reactive oxygen species (ROS) levels, and further decreased the activities of antioxidases after 96 h, causing destruction of cell membrane integrity and nuclear structure. However, the other two binary mixtures uro + his and ace + his were both antagonistic to Phaeocystis globosa . The increase in the level of ROS indicated that the algal cells suffered from oxidative damage. The surplus ROS induced the increase in malondialdehyde (MDA) content and activities of antioxidant enzymes including superoxide dismutase (SOD) and catalase (CAT), all of which reached maxima after 72 h treatment. Transmission electron microscopy (TEM) analysis revealed that these nitrogen-containing compounds caused destruction of cell membrane integrity, chloroplasts and nuclear structure. The present study will provide useful information for the combined effect of algicidal compounds on the harmful alga Phaeocystis globosa . This is the first report to explore single and combined algicidal effects of three nitrogen-containing compounds against the harmful alga Phaeocystis globosa .